KORELASI KETERAMPILAN MEMBACA PEMAHAMAN TEKS EKSPOSISI DAN KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS X SMA NEGERI 2 PAINAN - Putri, Nabela; Emidar, Emidar (Universitas Negeri Padang, 2019)
ABSTRACT The purpose of this study is three. First, describing reading skills understanding the exposition text of class X students at SMA Negeri 2 Painan. Second, describing the exposition text writing skills of Grade X students in SMA Negeri 2 Painan, describing the correlation of reading skills in the text comprehension exposition and the writing text skills for grade X students of SMA Negeri 2 Painan. This type of research is quantitative with descriptive method. The design used is correlational design. The study population was grade X students of SMA Negeri 2 Painan who were enrolled in the 2018/2019 school year, which was 354 students. The study sample was determined by proportional random sampling of 15% of the population, namely 54 students. The research data is in the form of a reading skill test score understanding of the exposition text and the score of writing skills the text exposition. There are two instruments for this research, namely objective tests to measure reading skills, comprehension of text exposition and performance tests to measure for writing text skills. Text comprehension exposition, and writing skills in class X students of SMA Negeri 2 Painan at the real level (α) of 95% with n-1 freedom degrees in other words if the reading skills of students exposition text comprehension are good, then students' writing skills are also good. Conversely, if the reading skills of students exposition text comprehension are bad then the students' writing exposition text skills are also bad. Kata kunci : Keterampilan Membaca Pemahaman, Keterampilan Menulis Teks Eksposisi